Efficacy and Safety of Sublingual Cyclobenzaprine for the Treatment of Fibromyalgia: Results From a Randomized, Double‐Blind, Placebo‐Controlled Trial - Lederman, Seth; Arnold, Lesley M.; Vaughn, Ben; Kelley, Mary; Sullivan, Gregory M. (Arthritis care & research (2010), 2023)
To evaluate the efficacy and safety of TNX-102 SL, a once-nightly sublingual formulation of cyclobenzaprine, in reducing pain in patients with fibromyalgia (FM). RELIEF was a double-blind, randomized, placebo-controlled trial. Overall, 503 patients received TNX-102 SL 2.8 mg for 2 weeks, followed by 5.6 mg for 12 weeks (248 patients), or matching placebo (255 patients). The primary end point was change from baseline at week 14 in the weekly average of daily pain scores. Secondary end points included Patient Global Impression of Change (PGIC) scores, Fibromyalgia Impact Questionnaire Revised (FIQR) scores, Patient-Reported Outcomes Measurement Information System (PROMIS) Sleep Disturbance and Fatigue scores, and daily sleep quality. Safety was assessed by adverse event (AE) reporting. Reduction in daily pain from baseline at week 14 was significantly greater with TNX-102 SL (least squares [LS] mean change -1.9 [95% confidence interval (95% CI) -2.1, -1.7]) versus placebo (LS mean change -1.5 [95% CI -1.7, -1.3]; P = 0.01). TNX-102 SL was not associated with significant improvement in PGIC at week 14 but was associated with improvements in FIQR scores, PROMIS scores, and daily sleep quality. Overall, 59.7% of patients receiving TNX-102 SL and 46.3% receiving placebo reported treatment-emergent AEs; the most common were oral hypoesthesia (17.3% with TNX-102 SL versus 0.4% with placebo), oral paresthesia (5.6% versus 0.4%, respectively), and product taste abnormal (4.4% versus 0.4%, respectively). In this phase III, randomized, controlled trial of patients with FM, treatment with TNX-102 SL was associated with significant reductions in daily pain and was safe and well tolerated.